Simulation of Torsion Moment at the Wheel Set of the Railway Vehicle with the Traction Electromotor for Wavy Direct Current - Branislav S. Gavrilovic (Communications - Scientific letters of the University of Zilina, 2008)
The phenomenon of mechanical resonance in the axial make of the railway vehicle with the traction electromotors for wavy direct current has been of topical interest for the railway connoisseurs for a long time. This is not randomly because mechanical resonance may cause crevices and fractures in the wheel set. Accordingly mechanical resonance may endanger safety of railway communication. However, previous research did not precisely investigate the influence of tension and current at the value and guise of torsion moment at the wheel set. Therefore, this paper defined adduced influence. Besides, this paper defined the optimal antislippage shield for all the railway vehicles with the traction electromotors for wavy direct current.